THE APPLICATION OF THE PATH ANALYSIS MODEL IN DETERMINING THE EFFECT OF IQ AND LANGUAGE SKILLS ON MATHEMATICS LEARNING OUTCOME - Dewi Wulandari; Dewi Setyawati; Dhian Endahwuri (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2025)
Mathematics learning outcome is inseparable from many factors that influence it. Intelligence Quotient (IQ) and language skills are several factors that are thought to influence learning outcomes in mathematics. This study aims to determine the path analysis model of the mathematics learning outcome with IQ and language skill as the factors. The population of this research was all the students of Kesatrian I Junior High School, Semarang (SMP Kesatrian I Semarang), and by using a random sampling technique, we took 221 students as the sample. The result shows a significant influence of IQ and language skills on mathematics learning outcomes.